Advertisement Remove all ads

# Solve the Following Equation and Verify Your Answer: 2 X − ( 7 − 5 X ) 9 X − ( 3 + 4 X ) = 7 6 - Mathematics

Sum

Solve the following equation and verify your answer:

$\frac{2x - (7 - 5x)}{9x - (3 + 4x)} = \frac{7}{6}$
Advertisement Remove all ads

#### Solution

$\frac{2x - (7 - 5x)}{9x - (3 + 4x)} = \frac{7}{6}$

$\text{ or }\frac{7x - 7}{5x - 3} = \frac{7}{6}$

$\text{ or }42x - 42 = 35x - 21 [\text{ After cross multiplication }]$

$\text{ or }42x - 35x = - 21 + 42$

$\text{ or }7x = 21$

$\text{ or }x = \frac{21}{7}$

$\text{ or }x = 3$

$\text{ Thus, }x = 3\text{ is the solution of the given equation . }$

$\text{ Check: }$

$\text{ Substituting }x = 3\text{ in the given equation, we get: }$

$\text{ L . H . S . }= \frac{2 \times 3 - (7 - 5 \times 3)}{9 \times 3 - (3 + 4 \times 3)} = \frac{6 - (7 - 15)}{27 - (3 + 12)} = \frac{6 + 8}{27 - 15} = \frac{14}{12} = \frac{7}{6}$

$\text{ R . H . S . }= \frac{7}{6}$

$\therefore \text{ L . H . S . = R . H . S . for }x = 3 .$

Is there an error in this question or solution?
Advertisement Remove all ads

#### APPEARS IN

RD Sharma Class 8 Maths
Chapter 9 Linear Equation in One Variable
Exercise 9.3 | Q 18 | Page 17
Advertisement Remove all ads

#### Video TutorialsVIEW ALL 

Advertisement Remove all ads
Share
Notifications

View all notifications

Forgot password?
Course